An Economic Perspective on Higher Education in the United States (Economic and Political Thought, 2012)
The article presents the analysis of higher education in the United Statesand proves that the sources of success of the US higher education – incontrast with higher education sectors in other countries – are the freedomof universities to develop their own strategies, competition and relatively highlevels of funding. There are obvious lessons to be learned from the Americanexperience but their application requires creativity and sensitivity to localconditions rather than just an attempt to duplicate the American institutions,their policy and funding systems.